Product Development Model for Tempe Chocolate Chips Based on Costumer Preferences in Banjarnegara, Central Java, Indonesia - Hidayat, Hety Handayani; Wijayanti, Nur (Department of Agro-industrial Technology, University of Brawijaya, 2021)
AbstractThis study aims to determine the attributes and categories that are important in product development and its model to obtain appropriate design recommendations based on consumer preferences using Quantification Theory Type 1 (QTT1). The number of respondents involved was 250 respondents in Banjarnegara Regency who were selected on purposive sampling. Respondents were asked to rate the level of preference for 14 samples of chocolate tempe chips. The results of the identification of attributes and categories that affect preferences obtained seven attributes and 19 categories, namely shape attributes (round, square, triangle, and oval), thickness (thin and thick), size (large and medium), distinctive aroma (tempe, chocolate, and fruits), flavors (chocolate and variants), surface layers (glossy, sprinkles, sprinkles & chocolate, visible tempe surface & sprinkles), as well as coatings (chocolate compound coating and chocolate coating & sprinkles). Based on the data analysis, some recommendations for product development of chocolate tempe chips are: round, 0.15 mm thick, 8 cm wide, flavored and chocolatey, glossy coating with chocolate coating and sprinkles.Keywords: costumer’s preferences, product development model, tempe chocolate chips AbstrakPenelitian ini bertujuan untuk menentukan atribut hingga kategori yang penting dalam pengembangan produk dan memodelkannya untuk memperoleh rekomendasi desain yang sesuai berdasarkan preferensi konsumen dengan menggunakan Quantification Theory Type 1 (QTT1). Jumlah respoden yang terlibat sebanyak 250 responden di Kabupaten Banjarnegara yang dipilih dengan purposive sampling. Responden diminta untuk menilai tingkat preferensi terhadap 14 sampel produk keripik tempe cokelat. Hasil identifikasi atribut dan kategori yang memengaruhi preferensi diperoleh 7 atribut dan 19 kategori, yaitu atribut bentuk (bulat, kotak, segitiga, dan oval), ketebalan (tipis dan tebal), lebar (besar dan sedang), aroma khas (tempe, cokelat, dan buah-buahan), rasa (cokelat dan varian), lapisan permukaan (mengkilap, taburan, taburan & cokelat, serta tempe terlihat & ada taburan), serta pelapis (coating compound cokelat dan coating cokelat & taburan). Analisis data menghasilkan rekomendasi pengembangan produk keripik tempe cokelat adalah berbentuk bulat, tebal 0,15 mm, lebar 8 cm, beraroma dan berasa cokelat, lapisannya mengkilap dengan bahan pelapis coating cokelat dan taburan.Kata kunci: keripik tempe cokelat, model pengembangan produk, preferensi konsumen